Circulating Exosomal miR-181b-5p Promoted Cell Senescence and Inhibited Angiogenesis to Impair Diabetic Foot Ulcer via the Nuclear Factor Erythroid 2-Related Factor 2/Heme Oxygenase-1 Pathway - Wang, Shaohua; Shi, Min; Zhou, Jing; Wang, Wenjing; Zhang, Yuanyuan; Li, Yongjun (Frontiers in Cardiovascular Medicine, 2022)
Endothelial cell dysfunction is the main contributing factor of diabetic foot ulcer (DFU). Circulating exosomes have been found to play an important role in many processes, such as cell senescence and angiogenesis. However, the underlying roles and mechanism of circulating exosomes in the onset and progression of DFU remain unclear. In this study, we isolated exosomes from the plasma of patients with DFU (DFU-Exos) and non-diabetic foot wounds (NDF-Exos). DFU-Exos promoted cell senescence and inhibited tube formation in Human Umbilical Vein Endothelial Cells (HUVECs), unlike NDF-Exos. Several datasets suggest that miR-181b-5p expression might be enriched in exosomes from DFU; this was verified using quantitative real-time PCR (qRT-PCR). We also found that miR-181b-5p, which was taken up by HUVECs, promoted cell senescence and inhibited tube formation. Dual luciferase reporter assay, qRT-PCR, Western blotting, and immunofluorescence staining confirmed that miR-181b-5p could negatively regulate nuclear factor erythroid 2-related factor 2 (NRF2) expression by binding to its 3′ UTR, thus further suppressing heme oxygenase-1 (HO-1) expression. In addition, NRF2 and HO-1 inhibitors could also rescue the effects of senescence and tube formation exerted by miR-181b-5p inhibitor. In vivo experiments showed that exosomes isolated from HUVECs which inhibited miR-181b-5p expression promoted angiogenesis to further restore the capacity of wound healing. In conclusion, this study indicated that circulating exosomal miR-181b-5p promoted cell senescence and inhibited angiogenesis to impair wound healing in DFU by regulating the NRF2/HO-1 pathway.